HPV Involvement in Head and Neck Cancers: Comprehensive Assessment of Biomarkers in 3680 Patients - Castellsagué, Xavier; Alemany, Laia; Quer, Miquel; Halec, Gordana; Quirós, Beatriz; Tous, Sara; Clavero, Omar; Alòs, Llúcia; Biegner, Thorsten; Szafarowski, Tomasz; Alejo, Maria; Holzinger, Dana; et al. (JNCI : Journal of the National Cancer Institute, 2016)
We conducted a large international study to estimate fractions of head and neck cancers (HNCs) attributable to human papillomavirus (HPV-AFs) using six HPV-related biomarkers of viral detection, transcription, and cellular transformation. Formalin-fixed, paraffin-embedded cancer tissues of the oral cavity (OC), pharynx, and larynx were collected from pathology archives in 29 countries. All samples were subject to histopathological evaluation, DNA quality control, and HPV-DNA detection. Samples containing HPV-DNA were further subject to HPV E6*I mRNA detection and to p16(INK4a), pRb, p53, and Cyclin D1 immunohistochemistry. Final estimates of HPV-AFs were based on HPV-DNA, HPV E6*I mRNA, and/or p16(INK4a) results. A total of 3680 samples yielded valid results: 1374 pharyngeal, 1264 OC, and 1042 laryngeal cancers. HPV-AF estimates based on positivity for HPV-DNA, and for either HPV E6*I mRNA or p16(INK4a), were 22.4%, 4.4%, and 3.5% for cancers of the oropharynx, OC, and larynx, respectively, and 18.5%, 3.0%, and 1.5% when requiring simultaneous positivity for all three markers. HPV16 was largely the most common type. Estimates of HPV-AF in the oropharynx were highest in South America, Central and Eastern Europe, and Northern Europe, and lowest in Southern Europe. Women showed higher HPV-AFs than men for cancers of the oropharynx in Europe and for the larynx in Central-South America. HPV contribution to HNCs is substantial but highly heterogeneous by cancer site, region, and sex. This study, the largest exploring HPV attribution in HNCs, confirms the important role of HPVs in oropharyngeal cancer and drastically downplays the previously reported involvement of HPVs in the other HNCs.